Use and Outcomes of Dexamethasone in the Management of Malignant Small Bowel Obstruction - Frank F. Yang, MD; Elina Serrano, MD; Kyle S. Bilodeau, MD; Michael Weykamp, MD; Caitlin J. Silvestri, MD; Ashleigh C. M. Bull, MD; Brenda Lin, MD; Sara L. Schaefer, MD; Colette Galet, PhD; Luis J. Garcia, MD, FACS; Baraka Gitonga, BS; David T. Kolodziej, BS; et al. (Annals of Surgery Open)
Objective:. To describe rates of dexamethasone use in the nonoperative management of malignant small bowel obstruction (mSBO) and their outcomes. Background:. mSBO is common in patients with advanced abdominal-pelvic cancers. Management includes prioritizing quality of life and avoiding surgical intervention when possible. The use of dexamethasone to restore bowel function is recommended in the National Comprehensive Cancer Network guidelines for mSBO. Yet, it is unknown how often dexamethasone is used for mSBO and whether results from nonresearch settings support its use. Methods:. This is a multicenter retrospective cohort study including unique admissions for mSBO from January 1, 2019 to December 31, 2021. Dexamethasone use and management outcomes were summarized with descriptive statistics and multiple logistic regression. Results:. Among 571 admissions (68% female, mean age 63 years, 85% history of abdominal surgery) that were eligible and initially nonoperative, 26% [95% confidence interval (CI) = 23%–30%] received dexamethasone treatment (69% female, mean age 62 years, 87% history of abdominal surgery). Dexamethasone use by site ranged from 13% to 52%. Among dexamethasone recipients, 13% (95% CI = 9%–20%) subsequently required nonelective surgery during the same admission and 4 dexamethasone-related safety-events were reported. Amongst 421 eligible admissions where dexamethasone was not used, 17% (95% CI = 14%–21%) required nonelective surgery. Overall, the unadjusted odds ratio (OR) for nonelective surgery with dexamethasone use compared to without its use was 0.7 (95% CI = 0.4–1.3). Using multiple logistic regression, OR after adjusting for site, age, sex, history of abdominal surgery, nasogastric tube, and Gastrografin use was 0.6 (95% CI = 0.3–1.1). Conclusion:. Dexamethasone was used in about 1 in 4 eligible mSBO admissions with high variability of use between tertiary academic centers. This multicenter retrospective cohort study suggested an association between dexamethasone use and lower rates of nonelective surgery, representing a potential opportunity for quality improvement.